Effect of Bilateral Carotid Body Resection on Cardiac Baroreflex Control of Blood Pressure During Hypoglycemia. Issue 6 (June 2015) - Limberg, Jacqueline K.; Taylor, Jennifer L.; Mozer, Michael T.; Dube, Simmi; Basu, Ananda; Basu, Rita; Rizza, Robert A.; Curry, Timothy B.; Joyner, Michael J.; Wehrwein, Erica A.
Abstract : Hypoglycemia results in a reduction in cardiac baroreflex sensitivity and a shift in the baroreflex working range to higher heart rates. This effect is mediated, in part, by the carotid chemoreceptors. Therefore, we hypothesized hypoglycemia-mediated changes in baroreflex control of heart rate would be blunted in carotid body–resected patients when compared with healthy controls. Five patients with bilateral carotid body resection for glomus tumors and 10 healthy controls completed a 180-minute hyperinsulinemic, hypoglycemic (≈3.3 mmol/L) clamp. Changes in heart rate, blood pressure, and spontaneous cardiac baroreflex sensitivity were assessed. Baseline baroreflex sensitivity was not different between groups ( P >0.05). Hypoglycemia resulted in a reduction in baroreflex sensitivity in both the groups (main effect of time, P <0.01) and responses were lower in resected patients when compared with controls (main effect of group, P <0.05). Hypoglycemia resulted in large reductions in systolic (−17±7 mm Hg) and mean (−14±5 mm Hg) blood pressure in resected patients that were not observed in controls (interaction of group and time, P <0.05). Despite lower blood pressures, increases in heart rate with hypoglycemia were blunted in resected patients (interaction of group and time, P <0.01). Major novel findings from this study demonstrate that intact carotid chemoreceptors are essential for increasing heart rate and maintaining arterial blood pressure during hypoglycemia in humans. These data support a contribution of the carotid chemoreceptors to blood pressure control and highlight the potential widespread effects of carotid body resection in humans.